Analysis of the Effect of Fraud Pentagon on Financial Statement Fraud Using M-Score and F-Score: Analisis Pengaruh Fraud Pentagon Terhadap Financial Statement Fraud Menggunakan M-Score dan F-Score - Masitah, Dewi (Universitas Muhammadiyah Sidoarjo, 2024)
This study evaluates the influence of the Fraud Pentagon elements—pressure, opportunity, rationalization, capability, and arrogance—on the detection of financial statement fraud in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during 2017-2019. Utilizing a quantitative methodology, data was collected from documents and literature studies and analyzed through logistic regression. The findings reveal that financial stability measured by the M-Score and F-Score models is significantly impacted by pressure, whereas opportunity affects fraud detection when using the M-Score model, and arrogance is significant with the F-Score model. However, no significant effects were observed for opportunity with the F-Score, rationalization with both models, capability with both models, and arrogance with the M-Score. These results underscore the variable influence of different fraud elements on the detectability of fraudulent activities, suggesting a need for targeted anti-fraud strategies within SOEs. Highlights: Pressure's Role: Pressure directly impacts financial fraud detection in SOEs. Model Variability: Opportunity and arrogance influence fraud detection differently across M-Score and F-Score models. Ineffective Elements: Several fraud elements show no significant impact, indicating gaps in detection methods. Keywords: Fraud Detection, Financial Statement Fraud, M-Score, F-Score, SOEs